2016
DOI: 10.1039/c6ta01994c
|View full text |Cite
|
Sign up to set email alerts
|

Lead-free SnTe-based thermoelectrics: enhancement of thermoelectric performance by doping with Gd/Ag

Abstract: SnTe, with the same rock-salt structure as PbTe, is a potentially attractive thermoelectric material. Pristine SnTe has poor thermoelectric performance because of its very high hole concentration resulting from intrinsic Sn vacancies, which leads to a high thermal conductivity and a low Seebeck coefficient. In this work, the thermoelectric properties of SnTe were modified by doping with different contents of gadolinium and silver. It is found that SnTe doped with optimal gadolinium (i.e. Gd0.06Sn0.94Te) exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 33 publications
5
64
0
Order By: Relevance
“…As compared to pristine SnTe, each of these two strategies enables a ≈150% zT enhancement, which accumulates to a ≈300% improvement when both are applied. The obtained peak zT of 1.6 (as shown in Figure a) is record for SnTe in p‐type, which is actually one of the highest among known p‐type thermoelectrics other than IV‐VI semiconductors (as shown in Figure b) . This work opens new possibilities for further improving this material, as well as promotes SnTe as an eco‐friendly solution for PbTe thermoelectrics in p‐type.…”
mentioning
confidence: 61%
“…As compared to pristine SnTe, each of these two strategies enables a ≈150% zT enhancement, which accumulates to a ≈300% improvement when both are applied. The obtained peak zT of 1.6 (as shown in Figure a) is record for SnTe in p‐type, which is actually one of the highest among known p‐type thermoelectrics other than IV‐VI semiconductors (as shown in Figure b) . This work opens new possibilities for further improving this material, as well as promotes SnTe as an eco‐friendly solution for PbTe thermoelectrics in p‐type.…”
mentioning
confidence: 61%
“…It has already been reported that Bi substitution in GeTe solid state solutions can result in segregation of Bi-rich nanoprecipitates [39]. In addition, such types of inclusions can cause collective phonon scattering from nanoprecipitates, meso-structured grain boundaries, and other crystallographic defects that could pave the way for reduction in lattice thermal conductivity [7,49,52]. In this work, for heavily-doped GTS-Bi samples, an ultra-low lattice thermal conductivity of ~0.7 Wm −1 K −1 was achieved at 523 K. κtotal obtained for these doped crystalline materials; especially, the Bi-doped ones are essentially in the range with the κtotal values of some of the well-known effective thermoelectric materials [15,42,49,53,54,55,56,57].…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports have demonstrated that the optimal maximum temperature for investigating the thermal and thermoelectric properties of SnSe is around 800 K due to the presence of the visible and invisible microgaps along the cleavage plane in the specimen arising from the shrinkage of the unit cell over 800 K caused by the phase transition. [27][28][29] In our work, L is calculated from the equation L = 1.5 + exp [−|α|/116], where L is in 10 −8 W Ω K −2 and α in µV K −1 . The total thermal conductivity is composed of the electronic thermal conductivity (κ ele ) and the lattice thermal conductivity (κ lat ).…”
Section: Thermoelectric Properties Of Pristine Ag-and Sncl 2 -Doped mentioning
confidence: 99%